Changing patterns of cardiovascular diseases and cancer mortality in Portugal, 1980-2010 - Pereira Marta; Peleteiro Bárbara; Capewell Simon; Bennett Kathleen; Azevedo Ana; Lunet Nuno (BMC, 2012)
Abstract Background Cardiovascular diseases and cancer are jointly responsible for more than half all deaths in Portugal. They also share some important risk factors and act as mutual competing risks. We aimed firstly to describe time trends in death rates and years of life lost due to cardiovascular diseases and cancer in the Portuguese population from 1980 to 2010; and secondly to quantify the contribution of the variation in population and age structure, and age-independent "risk" by cardiovascular or oncological causes to the change in the corresponding number of deaths. Methods We estimated the annual percent change in age-standardized mortality rates from cardiovascular diseases and cancer, in each sex. The specific contribution of demographic changes (due to changes in population size and in population age structure) and the variation in the age-independent "risk" of dying from the disease to the observed trends in the number of deaths was quantified using the tool RiskDiff. Years of life lost were computed using the Global Burden of Disease method. Results Among men, the mortality rate from all cardiovascular diseases was more than two-fold higher than cancer mortality in 1980. However, three decades later mortality from cancer surpassed cardiovascular diseases. After 2005, the years of life lost from cancer were also higher than from cardiovascular diseases. Among women, despite the decrease in death rates, cardiovascular diseases remained the leading cause of death in 2010 and their absolute burden was higher than that of cancers across the whole period, mainly due to more events in older women. Conclusions In Portugal, the 20th century witnessed a dramatic decrease in the cardiovascular disease mortality and YLL, and the transition towards cancer. In more recent years, the highest burdens of disease came from cancers in men and from cardiovascular diseases in women.